Evaluation of Two Rapid Lateral Flow Tests and Two Surrogate ELISAs for the Detection of SARS-CoV-2 Specific Neutralizing Antibodies - Girl, Philipp; Zwirglmaier, Katrin; von Buttlar, Heiner; Wölfel, Roman; Müller, Katharina (Frontiers in Medicine, 2022)
As vaccination against SARS-CoV-2 progresses rapidly around the world, reliable detection of SARS-CoV-2 specific neutralizing antibodies (NAb) has become an indispensable component of serological diagnostics. We evaluated the performance of four commercially available tests, i.e. two lateral flow assays (Coris BioConcept COVID-19 Sero NP/RBD and Concile InfectCheck COVID-19 NAb) and two surrogate ELISA (sELISA) tests (EUROIMMUN SARS-CoV-2 NeutraLISA and AdipoGen SARS-CoV-2 Neutralizing Antibodies Detection Kit) in comparison with an in-house SARS-CoV-2 micro neutralization test as reference. A total of 334 sera were tested, including 30 samples collected prior to the emergence of SARS-CoV-2, 128 sera from convalescent patients as well as 176 sera from partially or fully vaccinated individuals. The overall sensitivity of LFAs differed and was 71.6% for the Coris and 98.4% for the Concile. In contrast, overall sensitivity of the NeutraLISA was 86% and 98% for the AdipoGen. All test showed the highest sensitivity when testing samples from fully vaccinated individuals with both sELISA achieving 100% sensitivity. Overall specificity was 89.3% for the Coris and only 58.3% for the Concile. Similarly, significant differences were observed for both sELISA, with an overall specificity of 82.1% for the NeutraLISA and only 54.8% for the AdipoGen. All tests showed a 100% specificity when testing negative control samples while specificities were lowest when testing samples from only partially vaccinated individuals.